An unusual periodontal abscess - A Case report - A V Saravanan; K H Panishankar; Prem Alex Lawrence (Wolters Kluwer Medknow Publications, 2012)
Periodontal abscess is a bacterial infection that most often develops in the periodontium, a supporting structure that is between the teeth and the gums. It can also develop elsewhere but at first doesn't affect the main structure of the tooth, though it can cause tooth pain. Other symptoms besides the gum boil could occur, and they may include discomfort chewing on the side of the mouth where it is present or a sensation of pain at all times. Gum boils can rupture or they can simply enlarge. It's also possible for the periodontal abscess to spread to the mouth or sinuses during rupture or prior and cause a much more complicated condition. This is a report of one such case of a periodontal abscess which presented as a swelling on the left side of the cheek in a forty eight year old man. We present this as a rare case.